HDV RNA assays: Performance characteristics, clinical utility, and challenges - Wedemeyer, Heiner; Leus, Mitchell; Battersby, Thomas R.; Glenn, Jeffrey; Gordien, Emmanuel; Kamili, Saleem; Kapoor, Hema; Kessler, Harald H.; Lenz, Oliver; Lütgehetmann, Marc; Mixson-Hayden, Tonya; Simon, Christian O.; et al. (Hepatology (Baltimore, Md.), 2025)
Coinfection with HBV and HDV results in hepatitis D, the most severe form of chronic viral hepatitis, frequently leading to liver decompensation and HCC. Pegylated interferon alpha, the only treatment option for chronic hepatitis D for many years, has limited efficacy. New treatments are in advanced clinical development, with one recent approval. Diagnosis and antiviral treatment response monitoring are based on detection and quantification of HDV RNA. However, the development of reliable HDV RNA assays is challenged by viral heterogeneity (at least 8 different genotypes and several subgenotypes), intrahost viral diversity, rapid viral evolution, and distinct secondary structure features of HDV RNA. Different RNA extraction methodologies, primer/probe design for nucleic acid tests, lack of automation, and overall dearth of standardization across testing laboratories contribute to substantial variability in performance characteristics of research-based and commercial HDV RNA assays. A World Health Organization (WHO) standard for HDV RNA, available for about 10 years, has been used by many laboratories to determine the limit of detection of their assays and facilitates comparisons of RNA levels across study centers. Here we review challenges for robust pan genotype HDV RNA quantification, discuss particular clinical needs and the importance of reliable HDV RNA quantification in the context of drug development and patient monitoring. We summarize distinct technical features and performance characteristics of available HDV RNA assays. Finally, we provide considerations for the use of HDV RNA assays in the context of drug development and patient monitoring.